Descriptions of Scientific Literacy Skills of 9th Grade of Secondary School Students on Human Excretory System - Siti Darmi Amir; Sitti Rahma Yunus; Hasanuddin Hasanuddin; Ramlawati Ramlawati; Sitti Saenab (Universitas Muhammadiyah Sidoarjo, 2023)
This study is a quantitative descriptive survey research that aims to describe the level of scientific literacy skills of ninth-grade of secondary school students’ in Angkona sub-district accredicted A and B for 2021/2022 academic year in terms of context, knowledge, and scientific competence on human excretory system topics. Population of this study were all ninth grade of secondary school students accredicted A and B throughout in Angkona sub-district with 252 students, namely SMPN A which was accredicted A; and SMPN B, C, and D were accredicted B. Samples were selected using saturated sample technique so that the samples in this research were 252 students. The instrument of this research was 20 multiple choice questions on human excretory system topics. The data collection technique was by giving tests directly at school and/or giving online test for students who did not come to school via Google Form and/or WhatsApp. The data were analyzed using analysis of quantitative descriptive. The results obtained are the scientific literacy skills of ninth-grade of secondary school students in Angkona sub-district: (1) in the context of science is in “medium”, (2) knowledge of science is in the “medium”, and (3) competence of science is in the “low” category.